2022
DOI: 10.1039/d1sc04277g
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic vs. inductive effects in phosphine ligand donor properties and reactivity

Abstract: Enhanced rates and selectivity in enzymes are enabled in part by precisely tuned electric fields within active sites. Analogously, the use of charged groups to leverage electrostatics in molecular systems...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 141 publications
(287 reference statements)
0
14
0
3
Order By: Relevance
“…The fluxional nature of the ethyl linkage may support a varied distance between 9BBN and the iron core, and so it appears that none of these configurations makes a measurable contribution to E p,c . We note however that it is known that redox-inactive Lewis acid SCS groups can have significant effects on reaction outcomes, as in homogeneous CO hydrogenation, , and in C–F bond activation chemistry, and we hope that future studies on the reactivity of 2 – might uncover effects that are not related to the E p,c of 2 – .…”
Section: Resultsmentioning
confidence: 93%
“…The fluxional nature of the ethyl linkage may support a varied distance between 9BBN and the iron core, and so it appears that none of these configurations makes a measurable contribution to E p,c . We note however that it is known that redox-inactive Lewis acid SCS groups can have significant effects on reaction outcomes, as in homogeneous CO hydrogenation, , and in C–F bond activation chemistry, and we hope that future studies on the reactivity of 2 – might uncover effects that are not related to the E p,c of 2 – .…”
Section: Resultsmentioning
confidence: 93%
“…16 Top: major resonance contributors to the ground state of a novel phosphine selenide architecture bearing an appended -BF 3 À unit. 94 Bottom: the computational use of a point charge near a neutral varient (-Et) of the phosphine was needed to mimic experimental observables for the properties of the phosphine selenide.…”
Section: Intermolecular Electrostatic Interactions In Homogeneous Sys...mentioning
confidence: 99%
“…The inductive and electrostatic properties of this unique, anionic phosphine were studied through its use as a ligand on nickel/rhenium and through the formation of a phosphine selenide. 94 This latter species was studied in detail, and analysis of its 1 J PSe NMR coupling constants in a variety of solvents revealed a dramatic dependence on the solvent dielectric constant. Since the R 3 P]Se interaction exhibits signicant ylidic character in the form of R 3 P + -Se À , the impact of the solvent dielectric on 1 J PSe suggested that local ESFs emanating from the borate group impact the ground state of the molecule.…”
Section: Molecular Electrostatic Effects In Small Molecule Activation...mentioning
confidence: 99%
“…A more suitable system involves the oxidation of a phosphine to its phosphine selenide and analyzing the 1 JPSe spin-spin coupling constants via 31 P-NMR. [54][55][56]182,183] The methodology shows good correlation to the TEP and basicity of the phosphine and shows high selectivity towards phosphorus oxidation. However, to ensure its validity bulky moieties at the phosphorus and hydrogen bonds towards the selenium should be avoided.…”
Section: Phosphine Selenides and 1 Jpse Coupling Constantsmentioning
confidence: 99%
“…However, using a solvent with smaller dielectrics should decrease the medium's ability to shield the charge, which should result in an increase of the 1 JPSe spin-spin coupling constant for cationic charges (electrostatic effect). [183] This effect should not be present for neutral phosphines or reversed for anionic phosphines. The increase of 1 JPSe can be seen in the case of Na + , Mg 2+ , Zn 2+ and Ru 2+ .…”
Section: Scheme 85: Strategies Towards Phosphine Selenidesmentioning
confidence: 99%